KAJIAN SOSIO YURIDIS TERHADAP PERKAWINAN ANAK DI BAWAH UMUR STUDI KASUS PADA KECAMATAN MARAWOLA - Hanafi, Suhri; Hamiyuddin, Hamiyuddin (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
This study was entitled "The juridical socio-marriage study under theage of Marawola district‛ This study aims to describe the factors thatcause the occurrence of marriage of children under the age thatoccurred in Marawola district. The results of this study indicate thatsubstantively the occurrence of young marriage in adolescents in somevillages in the district marawola district is a complex problem that cannot be separated from social problems, economic, religious culture.This means that the occurrence of young marriage associated withvarious factors such problems. parents' concerns about the currentpatterns of intercourse encourage parents to immediately marry offtheir children. This research becomes an ingredient for parents, so asnot to rush to marry off minors (adolescents). Because adolescentshave not been able to deal with and solve the problems of thehousehold well. The teenagers still need a lot of good stock of physicalmaturity, mental and social economy, general science, religion, lifeexperiences in married life. The study was conducted in MarawolaDistrict of Sigi Regency.